PTU-080 Efficacy and Safety of Obeticholic Acid (OCA) in PBC Patients with Advanced Disease as Evidenced by Abnormal Bilirubin: An Integrated Analysis. (17th August 2016) - Jones, D; Chapman, R; Thorburn, D; Dillon, JF; Ryder, SD; Hirschfield, G; Mells, G; Carbone, M; Pencek, R; Hooshmand-Rad, R; Shapiro, D
Abstract : Introduction: ALP and bilirubin are both strongly associated with need for liver transplant or death in patients with primary biliary cirrhosis (PBC, also known as primary biliary cholangitis). Elevation of ALP precedes elevations in bilirubin, which is of particular concern since bilirubin is the major predictor of adverse disease outcome. Obeticholic acid (OCA, 6 ethyl chenodeoxycholic acid) is a selective potent FXR agonist developed for treatment of PBC. Given the particular concern in patients with abnormal bilirubin, the intent of this analysis was to evaluate the efficacy and safety of OCA in patients with an elevated bilirubin. Methods: The clinical development of OCA in PBC has included three randomised, double-blind, placebo-controlled studies (2 Phase 2 trials and 1 Phase 3). Abnormal bilirubin was not a common feature in the individual studies, therefore, data from all three studies was pooled. All studies included key biochemical and clinical assessments at 3 months of OCA therapy; data was also available for a subset of subjects at 12 months. Results: ALP was markedly elevated at baseline in patients with abnormal bilirubin and OCA treatment was associated with significant ALP reductions. Bilirubin levels increased in the placebo arm and decreased with OCA, although the difference was not statistically significant over this short 3 month timeframe. At 12 months there was a significant reduction in bilirubin vs. placebo. Consistent with the overall population, pruritus was the most common event in placebo and OCA-treated patients. The safety profile of OCA was consistent with the overall development program. Hepatic disorders (eg, increased bilirubin, PBC, and postal hypertension) and serious adverse events increased in incidence with abnormal bilirubin levels but were likely due to progression of the underlying disease. Conclusion: OCA treatment in patients with advancing disease, as evidenced by abnormal bilirubin, was associated with significant improvements in ALP and bilirubin, parameters shown to correlate with improved clinical outcome. Disclosure of Interest: None Declared